Prediction of Local Scour Rate around Bridge Piers Using SSIIM Model - Abdeldayem, Ahmad W.; Elsaeed, Gamal H.; Toukhy, Mahmoud A.R. El; Ghareeb, Ahmed A. (IJRDO-Journal of Applied Science, 2015)
Scouring around bridge piers phenomena are studied by several researchers. They proved that SSIIM(Sediment Simulation In Intakes with Multi-block option) model is a powerful tool in predicting local scouraround rectangular piers for clear water scour. The main objective of this paper is to verify SSIIM model inpredicting the local scour for live bed and clear water scour around bridge piers. Also, it covered predictionof scour for circular and rectangular piers with different sizes. In addition the predicted scour rate wascompared with the scour rate obtained from experimental results by Sharafaddin A.A.S. (2003). All resultswere represented in curves. These curves showed good agreement between the predicted values by SSIIMand the experimental results. Moreover, the final scour values were in a good agreement with the valuescalculated by the most famous scour equation.